Penentuan Ukuran Pemesanan Material dengan Memperhatikan Decay Inventory dan Quantity Unit Discount - William Surya Wijaya; I Gede Agus Widyadana (Jurnal Titra, 2013)
In this paper we develop decay inventory with quantity unit discounts models. The models are built by considering purchasing and saving cost. The models are compared with Wagner Within model. The analyzes are conducted using a sensitivity analysis to changes in deteriorating rate, setup cost, inventory cost, purchase cost and changes in the number of demand. The model analysis is done by generating 50 random data. Result from the study shows that savings cost model 1.4% is better than purchasing cost model. The cost of Wagner Within model is 1.5% lower than the model with purchasing cost and not significantly different than the model that consider the savings cost.